Dynamic behaviour and energy dissipation of offline air pockets in transient pipe flows - Yun-Jie Li; Ling Zhou; Zhao Li; Tong-Chuan Che; Pedro Jose Lee; Yan-Qing Lu; Yin-Ying Hu (Engineering Applications of Computational Fluid Mechanics)
The traditional one-dimensional (1D) model often fails to accurately predict the dynamic pressure response of large offline air pockets during transients, due to a lack of comprehensive understanding of the underlying mechanisms of transient interaction with offline air pockets. This study investigated dynamic behavior and energy dissipation of offline air pockets through experiments and numerical models. Experimental pressure responses were predicted using a 1D-3D coupling model, which presented superior performance compared to traditional 1D model. The 1D-3D coupling model was further utilized to investigate the air-water interface, internal energy and turbulence distribution of offline air pockets. The results reveal that the stability of the air-water interface depends on the decelerating distance of the jet in offline tube, explaining the instability phenomenon with lower water levels observed in experimental snapshots. The internal energy pattern suggests different energy dissipation mechanisms compared to the inline air pockets. The distribution of turbulence intensity and effective thermal conductivity indicates significant additional energy dissipation at the inlet and outlet of offline neck. By incorporating a minor head loss term for offline neck into traditional 1D model, the pressure response aligns well with the results obtained from  1D-3D coupling model under different flow rates and air volumes.